Digital literacy in university students of education degrees in Ecuador - Pegalajar Palomino, Maria del Carmen; Rodríguez Torres, Ángel F. (Frontiers in Education, 2023)
Digital technologies have transformed the social and, consequently, educational context. Given this situation, it is worth highlighting the importance of promoting digital literacy to actively participate in the society in which it develops. This work analyzes the level of mastery of digital skills of the university students in Ecuador. To do this, a descriptive methodology has been used, based on the survey technique, based on a questionnaire (n = 778). Results reveal how the students give priority to research and information management, presenting difficulties in the development and adaptation of technological materials, as well as in the creation and adaptation of digital content. It even highlights how male university education students claim to have better digital skills, while the same situation is not the case for those others who study Intercultural Bilingual Education. This analysis enables Higher Education institutions to make decisions for planning, developing and acquiring digital skills in the university students of Education in Ecuador, in favor of better teaching professional development.